Loss of olfactory function after exposure to barbituric acid - Heiser, Clemens; Grupp, Kathrin Frauke; Hörmann, Karl; Stuck, Boris (Auris, nasus, larynx, 2010)
In this case report a patient with anosmia due to occupational exposure to barbituric acid will be presented. Occupational exposure to high concentrations of barbituric acid resulted in bloody nasal secretion and nasal itching with immediate onset following exposure. After several days of exposure, a progressive loss of smell resulted in anosmia. Psychophysical and electrophysiological assessment of olfactory function with the “Sniffiń Sticks” test and event-related potentials based on air dilution olfactometry confirmed the patients’ reports. After 2 years no recovery is remarked. Toxic anosmia has repeatedly been described due to exposure to chemicals, although barbituric acid has not been reported to be the cause of anosmia to date. Awareness of clinicians to toxic anosmia and the report of those cases appear to be mandatory to reduce occupational risks.